The impact of state and national standards on K-12 science teaching - Sunal, Dennis W.; Wright, Emmett (Research in science education., 2006)
This book addresses the expectations toward the science standards of various stakeholders including students, parents, teachers, administrators, higher education science and science education faculty members, politicians, governmental and professional agencies, and the business community. This book also investigates how the science standards have been translated into practice at the K-12 school district level, addressing issues around professional development, curriculum, assessment/evaluation, and accountability. The fundamental questions to be addressed are: (1) What is the response in terms of trends and patterns, of the educational system to the introduction of the national and state science standards since the late 1980's? and (2) What is the impact of the introduction of the science standards on teachers, classrooms, and students?